THE DYNAMICS OF INTERPERSONAL RELATIONSHIPS AND THE INFLUENCE ON STUDENT LEARNING MOTIVATION AT MA MA'ARIF AL ASY'ARI - Laily Divia Amlati; Khumairo Wardatul Jannah; Risqi Dwi Cahyati (Yayasan Amanah Nur Aman, 2026)
This study examines the phenomenon of students' emotional attraction at MA Ma'arif Al Asy'Ari which is often considered an obstacle to concentration, but psychologically has a strong influence on learning behavior. The main issue raised is the existence of rigid school policies on students' social relations, even though peer support is a key motivational factor. The purpose of this study is to map how the different interaction loci – internal and external to the school – affect the dynamics of student learning enthusiasm. Using a qualitative approach to phenomenological design, data were collected through participatory observation and in-depth interviews with teachers and students on April 22–23, 2026. The results show a pattern of impact dualism: the Internal-Class relationship functions as a positive catalyst through a mechanism of physical proximity (propinquity) that creates an intellectual